Cardiac sympathetic nerve stimulation enhances cardiovascular performance during hyperkalaemia in the anaesthetized pig. - O'Neill, M; Dorrington, K; Paterson, D (1993)
A rapid increase in arterial plasma potassium concentration to values seen during intense exercise depresses cardiac function at rest. Increasing the cardiac concentration of noradrenaline by right-sided sympathetic stimulation in eleven anaesthetized pigs significantly augmented cardiovascular performance during hyperkalaemia, while electrical pacing of the right atrium at equivalent rates to sympathetic stimulation afforded no protection against the deleterious effects of hyperkalaemia. We conclude that the inotropic effect of sympathetic activation may be important in sustaining cardiac function during exercise-induced hyperkalaemia.